2013
DOI: 10.1155/2013/185425
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia Modified Albumin Can Predict Necrosis at Incarcerated Hernias

Abstract: Purpose. To evaluate the predictive effect of IMA in incarcerated hernias. Methods. Three groups (n = 7) of rats were operated. Group I aimed to mimic incarceration, group II aimed the strangulation, and group III was the sham group. IMA and LDH measurements were made. Results. IMA levels were significantly higher in strangulation mimicking group and IMA levels were normal at postoperative 6th hour in incarceration mimicking group. LDH levels were significantly higher in both incarceration and strangulation mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…This indicates that the decision‐making, including start of emergency operation, should take place within 19 h from the onset of symptoms. This is supported by previous adult studies in which 12–24 h from onset of initial symptom to operation, was noted as the optimal time to avoid bowel resection . Additionally, Barkin reported that severe abdominal pain lasting >6 h in a patient who was previously well usually requires surgery .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This indicates that the decision‐making, including start of emergency operation, should take place within 19 h from the onset of symptoms. This is supported by previous adult studies in which 12–24 h from onset of initial symptom to operation, was noted as the optimal time to avoid bowel resection . Additionally, Barkin reported that severe abdominal pain lasting >6 h in a patient who was previously well usually requires surgery .…”
Section: Discussionsupporting
confidence: 69%
“…This is supported by previous adult studies in which 12-24 h from onset of initial symptom to operation, was noted as the optimal time to avoid bowel resection. [16][17][18] Additionally, Barkin reported that severe abdominal pain lasting >6 h in a patient who was previously well usually requires surgery. 19 Indeed, in the present study, the shortest interval to bowel resection in strangulation was 8 h.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia, reperfusion, acidosis and reactive oxygen radicals produced in the process of hypoxia are thought to cause these structural changes . IMA is regarded as a useful biomarker of oxidative stress and as a marker for diseases related to inflammation and vascular endothelial cell dysfunction . IMA is a sensitive biochemical marker for myocardial ischemia, muscle ischemia, pulmonary embolism, metabolic syndrome, hypercholesterolemia, mesenteric ischemia and cerebral ischemia .…”
Section: Discussionmentioning
confidence: 99%
“…40 IMA is regarded as a useful biomarker of oxidative stress and as a marker for diseases related to inflammation and vascular endothelial cell dysfunction. [41][42][43][44] IMA is a sensitive biochemical marker for myocardial ischemia, muscle ischemia, pulmonary embolism, metabolic syndrome, hypercholesterolemia, mesenteric ischemia and cerebral ischemia. 45,46 At the beginning of ischemia, IMA starts to increase and returns into normal values within 24 hours.…”
Section: Immune Complex Accumulation In Small Vessels Activates Inflamentioning
confidence: 99%
“…IMA has been tested as a potential marker of bowel ischemia, as detected by cobalt binding assay, with some level of efficiency [ 9 , 10 ]. It is sensitive enough to detect small areas of bowel ischemia during hernia incarceration in animal experiments [ 11 ].…”
Section: Introductionmentioning
confidence: 99%